Assessing Target Zone Credibility : Mean Reversion and Devaluation Expectations in the EMS - Svensson, Lars (IMF Working Papers; Working Paper ;, 1991)
The paper presents estimates of devaluation expectations for six EMS currencies relative to the Deutsche mark, for the period March 1979-May 1990. The estimation method is simple and operational, and consistently generates sensible results. The estimates are constructed by the adjusting interest rate differentials by subtracting estimated expected rates of depreciation within the exchange rate band. The adjustment is nontrivial because exchange rates within the ERM bands display mean reversion rather than random walk (unit root) behavior. The adjustment is essential since the expected rates of depreciation are usually of about the same magnitude as the interest rate differentials.